Perbandingan Hukum Tugas dan Kewenangan Notaris di Negara dengan Sistem Hukum Civil Law dan Common Law - Dewatoro Suryaningrat Poetra; Fendi Setyawan; Bhim Prakoso (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
A notary is a public official, a person becomes a public official when he is appointed and dismissed by the government and given the authority and obligation to serve the public in certain matters. Notarial institutions recognize two legal steles, namely the Continental (Latin) stelsel with the Civil Law system and the Anglo-Saxon stelsel with the Common Law system. Notarieship as well as regulations related to notarial practice have developed in accordance with time, place and legal politics and legal awareness in their respective countries. The differences and similarities in the nature, function, strength of evidence and implementation of notarial deeds in notarial practice in the two legal systems, especially between Indonesia as a country with a Civil Law legal system and countries with a Common Law legal system are interesting to study, for example Malaysia, England and the United States. In this research, a statute approach, conceptual approach and case approach are used. The statute approach is carried out by reviewing all laws and regulations related to the legal issues being addressed.